Upaya Meningkatkan Hasil Belajar Materi IPAS Bagian Mata Menggunakan Pembelajaran Koperatif Tipe (TGT) dengan Media Puzzle - Panca Agustina, Nadia; Zuhdi, Ulhaq; Sutiana, Sutiana; Imanayah, Dewi; Suwarno, Joko (Journal of Comprehensive Science, 2024)
This study aims to improve student learning outcomes in elementary schools through the application of the cooperative learning model Team Games Tournament (TGT) combined with puzzle media. TGT is a well-known learning strategy that encourages student participation by blending competition and collaboration, which has proven effective in various educational contexts. This classroom action research involved 30 fifth-grade students at SDN Ketabang 1, Surabaya. The research was conducted in two cycles, where TGT and puzzle media were used to teach science topics related to the human eye. Results showed a significant improvement in learning outcomes, with average student scores increasing from 55% in the pre-cycle to 85% by the end of the second cycle. Moreover, students’ engagement and social skills, such as teamwork and communication, were positively impacted. The study demonstrates that combining TGT with interactive media like puzzles not only enhances academic performance but also fosters a collaborative and engaging learning environment.